Formação e educação popular no campo entre a Igreja Católica e o Estado (1954-1964) - Stein, Leila de Menezes [UNESP] (My University, 2013)
In Brazil, the Catholic Church has an important role in the construction of citizenship, education and training the rural lower classes of the population. Studied in this article, this participation and contribution in the 60s, by highlighting the strong weighting would take the issue of land reform. The Catholic Church was a major player in unionization campaigns and basic education and suffered great tensions and internal conflicts that divide between those who sought the "liberation of the oppressed" and those who fought for reforms without changing the "social order". This paper recovers the trajectory of implementation of various programs of Catholic union formation and foundation of unions. We use historical methodology and retrieve the voice of the authors through interviews with trade unionists, lawyers, church authorities and militants popular.

No Brasil a Igreja Católica teve papel relevante para a construção da cidadania, educação e formação das camadas populares rurais da população. Estudamos, nesse artigo, essa participação e contribuição na década de 60, colocando em destaque a forte ponderação que assumiria a questão da reforma agrária. A Igreja Católica seria um dos principais atores nas campanhas de sindicalização e de educação de base e sofreria grandes tensões e conflitos internos que a dividiriam entre aqueles que buscavam a “libertação dos oprimidos” e os que lutavam por reformas sem alterar a “ordem social”. Recupera-se a trajetória de implantação de diversos programas católicos de formação sindical e de fundação de sindicatos. Utilizamos a metodologia histórica e recuperamos a voz de seus autores através de entrevistas com sindicalistas, com advogados, autoridades eclesiásticas e militantes populares.
Popular education and training in the field between the Catholic Church and State (1954-1964)
Keywords: Union formation; agrarian reform; Movimento Circulista; Ação Popular; Movimento Circulista; formação sindical; Ação popular; Reforma Agrária